1998
DOI: 10.1007/s004390050839
|View full text |Cite
|
Sign up to set email alerts
|

Functional defects of Cx26 resulting from a heterozygous missense mutation in a family with dominant deaf-mutism and palmoplantar keratoderma

Abstract: Mutations in GJB2 encoding the gap junction protein connexin-26 (Cx26) have been established as the basis of autosomal recessive non-syndromic hearing loss. The involvement of GJB2 in autosomal dominant deafness has also been proposed, although the putative mutation identified in one family with both deafness and palmoplantar keratoderma has recently been suggested to be merely a non-disease associated polymorphism. We have observed a similar phenotype in an Egyptian family that segregated with a heterozygous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
247
1
2

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 267 publications
(270 citation statements)
references
References 41 publications
14
247
1
2
Order By: Relevance
“…167delT and 235delC, which are the most common mutations in the Ashkenazi Jewish populations and Japanese populations respectively, were not observed in our study. Our results indicate that the R75W mutation is most likely associated with the non-syndromic form of hearing loss rather than the syndromic hearing loss as reported earlier, 21 although the effect of genetic background cannot be ruled out. Identification of 18 mutations and seven polymorphisms in this study and a large spectrum of mutations and polymorphisms identified by earlier studies on Cx26, suggest that this gene is subject to a relaxed selection.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…167delT and 235delC, which are the most common mutations in the Ashkenazi Jewish populations and Japanese populations respectively, were not observed in our study. Our results indicate that the R75W mutation is most likely associated with the non-syndromic form of hearing loss rather than the syndromic hearing loss as reported earlier, 21 although the effect of genetic background cannot be ruled out. Identification of 18 mutations and seven polymorphisms in this study and a large spectrum of mutations and polymorphisms identified by earlier studies on Cx26, suggest that this gene is subject to a relaxed selection.…”
Section: Discussionsupporting
confidence: 70%
“…Two individuals were heterozygous for R75W, which was previously reported to be associated with dominant hearing loss and palmoplantar keratoderma. 21 Richard et al 21 found R75W in a heterozygous condition in an individual from the control group without skin disorder. Hearing levels of the control group individuals in this study were unknown, and individuals affected with hearing loss were likely to be present in the control group they studied.…”
Section: Cx26 Mutationsmentioning
confidence: 97%
“…These skin-disease-associated connexin mutants appear to either suppress wild-type gap junction channel activity by exerting a dominant-negative effect on wild-type connexins or a transdominant effect on other connexin proteins (Rouan et al, 2001), or represent gain-of-function variants (Richard et al, 1998;Bakirtzis et al, 2003;Essenfelder et al, 2004;Gerido et al, 2007;Lee et al, 2009). For example, mutant forms of Cx31 can traffic incorrectly and accumulate in organelles such as the ER, causing ER stress and activation of the unfolded protein response (UPR), which results in cell death (Tattersall et al, 2009).…”
Section: The Importance Of Gap Junctionsmentioning
confidence: 99%
“…Expression of the Golgiretained R142W Cx32 mutation in myelinating Schwann cells of transgenic mice resulted in decreased levels of wild type mouse Cx32 and caused demyelination (Jeng et al 2006). Furthermore, dominant Cx26 mutations that cause hearing loss suppressed channel activity of coexpressed wild type Cx26, but only those mutants additionally causing skin disease inhibited intercellular conductance of co-expressed wild type Cx43 (Richard et al 1998;Rouan et al 2001). Here we describe the expression of Cx31.3, the human ortholog of Cx29 (Altevogt et al 2002), and its relation to the other oligodendrocyte GJ proteins Cx32 and Cx47.…”
Section: Introductionmentioning
confidence: 99%